Histone Deacetylase Inhibitor Improves the Development and Acetylation Levels of Cat–Cow Interspecies Cloned Embryos - Wittayarat, Manita (Mary Ann Liebert, Inc., 2013)
Abnormal epigenetic reprogramming, such as histone acetylation, might cause low efficiency of interspecies somatic cell nuclear transfer (iSCNT). This study was conducted to evaluate the effects of trichostatin A (TSA) on the developmental competence and histone acetylation of iSCNT embryos reconstructed from cat somatic cells and bovine cytoplasm. The iSCNT cat and parthenogenetic bovine embryos were treated with various concentrations of TSA (0, 25, 50, or 100 nM) for 24 h, respectively, following fusion and activation. Treatment with 50 nM TSA produced significantly higher rates of cleavage and blastocyst formation (84.3% and 4.6%, respectively) of iSCNT embryos than the rates of non-TSA–treated iSCNT embryos (63.8% and 0%, respectively). Similarly, the treatment of 50 nM TSA increased the blastocyst formation rate of parthenogenetic bovine embryos. The acetylation levels of histone H3 lysine 9 (H3K9) in the iSCNT embryos with the treatment of 50 nM TSA were similar to those of in vitro–fertilized embryos and significantly higher (p<0.05) than those of non-TSA–treated iSCNT embryos (control), irrespective of the embryonic development stage (two-cell, four-cell, and eight-cell stages). These results indicated that the treatment of 50 nM TSA postfusion was beneficial for development to the blastocyst stage of iSCNT cat embryos and correlated with the increasing levels of acetylation at H3K9.